2005
DOI: 10.1242/dev.01563
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Disp1 is required in sonic hedgehog-expressing cells for paracrine activity of the cholesterol-modified ligand

Abstract: There was a reanalysis of data required to support the findings in Development 132, 133-142.We have repeated the facial analysis reported in Fig. 2 to provide the data required to support some of the original findings of this study (see Publisher's note). Our findings substantiate the original conclusions drawn from Fig. 2 of a dose-related genetic interaction between Disp1 and Shh alleles, and of the function of Disp1 within Shh-producing cells. Some differences are reported below, which might reflect slight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 48 publications
4
47
1
Order By: Relevance
“…S3G, transversal planes g and g′). These data indicate that long-range signaling but not juxtacrine signaling requires disp function, as has been described previously in both Drosophila and vertebrates (42,43). In P compartment cells lacking disp function, Hh levels increase in cell membranes (11) (Fig.…”
Section: Disp Is Required For Hh Release Through the Basolateral Plasmasupporting
confidence: 85%
“…S3G, transversal planes g and g′). These data indicate that long-range signaling but not juxtacrine signaling requires disp function, as has been described previously in both Drosophila and vertebrates (42,43). In P compartment cells lacking disp function, Hh levels increase in cell membranes (11) (Fig.…”
Section: Disp Is Required For Hh Release Through the Basolateral Plasmasupporting
confidence: 85%
“…3B). Mutant conditions for Rab11, Disp and Dlp also reduce the dispersion of Hh and reduce Hh signaling [18,24,41,57,59,60,80,81].…”
Section: Preparing Hh For Releasementioning
confidence: 99%
“…2S,X). In 2005, the McMahon laboratory reported that a re-examination of two papers published by their group in Development (Tian et al, 2004;Tian et al, 2005a) had revealed a duplication of Dr Tian's data in these papers. Following their analysis, the authors announced, with regret, that they must retract Tian et al (2004), and this retraction was published by Development in November 2005, along with their apology to the editors and readership of the journal (Tian et al, 2005b).…”
Section: δ2/c829fmentioning
confidence: 99%
“…Following their analysis, the authors announced, with regret, that they must retract Tian et al (2004), and this retraction was published by Development in November 2005, along with their apology to the editors and readership of the journal (Tian et al, 2005b). With respect to the second paper (Tian et al, 2005a), the authors' review, overseen by the Committee on Professional Conduct (CPC) for the Faculty of Arts and Sciences at Harvard University, found that the principal conclusions of the paper were supported by appropriate documentation but that the documentation for Fig. 2 was inadequate, requiring a replication of those data.…”
Section: δ2/c829fmentioning
confidence: 99%